How Can Social Emotional Learning Strategies with Mindfulness Techniques Improve Reading Literacy? - Viantho, Indriana; Nirmala, Sri Dewi (International Journal of Elementary Education, 2024)
According to national and international studies, students’ literacy in Indonesia performed in a low level. Given the literacy conditions of students in Indonesia, as described above, teachers play a crucial role in preparing students for the future, considering that importance of literacy skills in the 21st century. Therefore, this study aims to analyze how social emotional learning strategies using mindfulness techniques, namely the "STOP" technique, can improve students' reading literacy. The research was carried out on students at elementary schools with a sample of 30 students. The independent variable in this research is social emotional learning strategies, while the dependent variable is students' reading literacy. The research was carried out using a mindfulness technique called the "STOP" technique. The research design used is a quantitative research design. Data was collected using instruments in the form of observation sheets, questionnaires, interviews and written tests. The data analysis techniques used are descriptive analysis, normality test, homogeneity test, and t-test. Data analysis was carried out manually and also using the SPSS 22 application. The results obtained showed that the social emotional learning strategy could increase the competency level of most students from basic level to most proficient level. This proves that the social emotional learning strategy with mindfulness techniques, namely the "STOP" technique, provides an increase in students' reading literacy.